PELAKSANAAN TUGAS KEPALA DESA DALAM PEMBERDAYAAN MASYARAKAT DI DESA PEMANDANG KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU - Akmal Herizal; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Execution of duties of village heads in rural community development in Rokan IV Koto subdistrict spectator Rokan Hulu regency. the purpose of this study is to investigate the implementation of the tasks of village heads in rural community development in Rokan IV Koto subdistrict scenery of Rokan Hulu regency, to determine the factors that hinder the implementation of the duties of village heads in rural community developmentin Rokan IV Koto subdistrict spectator Rokan Hulu regency.This study uses the resources of the constitution number 6 Year 2014 at the law there are three variables that include community empowerment, rural development, improving people’s welfare. the next factors that affect the implementation of the duties of village heads in rural community development in Roka IV Koto subdistrict spectator Rokan Hulu regency not maximal socialization of empowerment, not all activities involving the empowerment of rural institutions, lack of knowledge of village institutions, this research uses descriptive quantitative approach.The results of this study, according to sources of the constitution number 6 Year 2014 is the empowerment of rural communities, rural development, and improve community. this can be seen from three variables: the empowerment of rural communities less than optimal because the village head only make temporary activities, rural development produces less good, and improve the welfare of the community because the community still many who do not have their own garden. conclusions village chief task execution results in empowering communities in rural districts spectator Rokan IV Koto Rokan Hulu regency categorize less optimal and as for the factors that affect the implementation of the duties of villageheads in community empowerment includes not maximal socialization of empowerment, not all empowerment activities involving institutions village, and the lack of knowledge of village institutios.Keywors: Duties of villge heads and community empowerment